Pengaruh Rendaman Air Rebusan KencurbTerhadap Penurunan Edema Kaki Pada Ibu Hamil Trimester III Di Wilayah Kerja Puskesmas Payung Sekaki Kota Pekanbaru: The Effect of Boiled Galangal Water Soaking on Reducing Leg Edema in Third Trimester Pregnant Women in the Payung Sekaki Community Health Center in Pekanbaru City - Sumia Arsita sari (JOURNAL OF MEDICAL AND HEALTH SCIENCE, 2024)
Edema in the legs is one of the common problems experienced by pregnantwomen, especially in the third trimester. Accumulation of fluid in the tissuecauses swelling which can cause discomfort and impaired mobility. Onealternative effort to overcome the problem of edema is to use natural ingredientssuch as aromatic ginger. The results of an initial survey on pregnant women in thethird trimester did not yet know the benefits of boiled aromatic ginger water toreduce edema in the legs. This study aims to determine the effect of soaking inboiled aromatic ginger water on reducing edema in the legs of pregnant women inthe third trimester in the Payung Sekaki Community Health Center Work Area.The research method used was a quasi-experimental design using a one grouppretest-posttest design. The population was 10 pregnant women who experiencededema, the sample taken using the Total Sampling technique was 10 respondents.The subjects of the study were pregnant women in the third trimester whoexperienced edema in the legs. Univariate and bivariate analysis data used pairedsample t-test. The results showed a significant decrease in the size of the edemaafter the treatment of soaking in boiled aromatic ginger at the Payung SekakiHealth Center in 2024 (p-value = 0.000). This shows that aromatic ginger hasanti-inflammatory and diuretic effects that have the potential to reduce swelling.This study concludes that soaking in boiled aromatic ginger water is effective inhelping to reduce leg edema in pregnant women in the third trimester, so it can bean alternative non-pharmacological treatment.